Guidelines for the diagnosis and treatment of pancreatic cancer in China (2021). Issue 2 (7th June 2021) - Yang, Yinmo; Bai, Xueli; Bian, Dapeng; Cai, Shouwang; Chen, Rufu; Cao, Feng; Dai, Menghua; Fang, Chihua; Fu, Deliang; Ge, Chunlin; Guo, Xiaochao; Hao, Chunyi; et al.
Abstract : Abstract: The incidence of pancreatic cancer has been rising worldwide, and its clinical diagnosis and treatment remain a great challenge. To present the update and improvements in the clinical diagnosis and treatment of pancreatic cancer in recent years, Chinese Pancreatic Association, the Chinese Society of Surgery, Chinese Medical Association revised the Guidelines for the Diagnosis and Treatment of Pancreatic Cancer in China (2014) after reviewing evidence-based and problem-oriented literature published during 2015–2021, mainly focusing on highlight issues regarding diagnosis and surgical treatment of pancreatic cancer, conversion strategies for locally advanced pancreatic cancer, treatment of pancreatic cancer with oligo metastasis, adjuvant and neoadjuvant therapy, standardized processing of surgical specimens and evaluation of surgical margin status, systemic treatment for unresectable pancreatic cancer, genetic testing, as well as postoperative follow up of patients with pancreatic cancer. Forty recommendation items were finally proposed based on the above issues, and the quality of evidence and strength of recommendations were graded using the Grades of Recommendation, Assessment, Development, and Evaluation system. This guideline aims to standardize the clinical diagnosis and therapy, especially surgical treatment of pancreatic cancer in China, and further improve the prognosis of patients with pancreatic cancer.